Spin-glass model with essential short-range competing interactions - Sorokov, S.I.; Levitskii, R.R.; Vdovych, A.S. (Condensed Matter Physics, 2005)
We consider a proton-glass model with an arbitrary range of competing interactions within two-particle cluster approximation for the free energy and within symmetric replica approach. We show that for the thermodynamic characteristics, the Gaussian approximation for distribution functions of cluster fields can be used. For a simpler proton-glass model with weak long-range interactions (linear approximation) we study the effect of the long-range interactions and random internal fields on the phase diagram and thermodynamics characteristics. It is shown that small fluctuations of internal fields can lead to essential smearing of proton-glass transition region. The adaptability of the theory for a description of proton-glasses of Rb₁₋x(NH₄)xH₂PO₄-type is discussed.